ANALISIS HASIL BELAJAR MATEMATIKA SISWA SETELAH DISELENGGARAKAN KURIKULUM 2013 PADA MATERI ATURAN SINUS DAN COSINUS DI KELAS X SMA NEGERI 1 PALOH KABUPATEN SAMBAS - Juli Aswan (Jurnal Inovasi Pendidikan dan Pengajaran (JIPP), 2022)
Based on the results of research that has been carried out with data calculations, data obtained, general conclusions in research on student mathematics learning outcomes after the 2013 Curriculum was held on the subject of sine and cosine rules in class X SMA Negeri 1 Paloh, Sambas Regency. With specific conclusions as follows: (1) Students' mathematics learning outcomes in the high category after the 2013 Curriculum was held on the sine and cosine rule material for class X SMA Negeri 1 Paloh, Sambas Regency with an average score of 86.83, the minimum value or the lowest score is 81 and the maximum value or the highest score is 94. (2) The students' mathematics learning outcomes are in the medium category after the 2013 Curriculum was held for the sine and cosine rule material in class X SMA Negeri 1 Paloh, Sambas Regency with an average value of 77.09, the minimum value or the lowest score is 75 and the maximum value or the highest value is 79. (3) The results of students' mathematics learning in the low category after the 2013 Curriculum was held for the sine and cosine rule material in class X SMA Negeri 1 Paloh, Sambas Regency with an average value is 67.15, the minimum value or the lowest value is 54 and the maximum value or the highest value is 73